The Effect Of Service Quality, Price And Store Environment On Customer Satisfaction At PT Benua Penta Global Medan - Steven Huwinata; Vincent; Wenny Meliani (Institute of Computer Science (IOCS), 2021)
The purpose of doing this research is to find out the reduced customer satisfaction at PT Benua Penta Global caused by Service Quality, Price and Store Environment. The theory to support the research is the theory according to experts related to Service Quality, Price and Store Environment. 18,000 customers are the population of this study and 99 customers will be the sample of this research which is obtained from the slovin formula and 30 customers outside the sample are used to perform the Valid test. The results showed that Service Quality, Price and Store Environment simultaneously and partially had a significant effect on Customer Satisfaction with a coefficient of determination of 24.3% and the remaining 75.